Influence of X-ray scatter radiation on image quality in Digital Breast Tomosynthesis (DBT). (November 2017) - Rodrigues, M.J.; Di Maria, S.; Baptista, M.; Belchior, A.; Afonso, J.; Venâncio, J.; Vaz, P.
Abstract: Digital breast tomosynthesis (DBT) is a quasi-three-dimensional imaging technique that was developed to solve the principal limitation of mammography, namely the overlapping tissue effect. This issue in standard mammography (SM) leads to two main problems: low sensitivity (difficulty to detect lesions) and low specificity (non-negligible percentage of false positives). Although DBT is now being introduced in clinical practice the features of this technique have not yet been fully and accurately assessed. Consequently, optimization studies in terms of choosing the most suitable parameters which maximize image quality according to the known limits of breast dosimetry are currently performing. In DBT, scatter radiation can lead to a loss of contrast and to an increase of image noise by reducing the signal-to-difference-noise ratio (SDNR) of a lesion. Moreover the use of an anti-scatter grid is a concern due to the low exposure of the photon flux available per projection. For this reason the main aim of this study was to analyze the influence of the scatter radiation on image quality and the dose delivered to the breast. In particular a detailed analysis of the scatter radiation on the optimal energy that maximizes the SDNR was performed for different monochromatic energies and voltages. To reach this objective the PenEasy Monte Carlo (MC) simulation tool imbedded in the general-purpose main program PENELOPE, was used. After a successful validation of the MC model with measurements, 2D projection images of primary, coherent and incoherent photons were obtained. For that, a homogeneous breast phantom (2, 4, 6, 8 cm) with 25%, 50% and 75% glandular compositions was used, including a 5 mm thick tumor. The images were generated for each monochromatic X-ray energies in the range from 16 keV to 32 keV. For each angular projection considered (25 angular projections covering an arc of 50°) the scatter-to-primary ratio (SPR), the mean glandular dose (MGD) and the signal difference to noise ratio (SDNR) were calculated with the aim to assess/determine in which conditions (i.e. energy, angular projection, breast thickness) the scatter radiation affects the image quality. The obtained results on the aforementioned quantities and topics will be reported. Highlights: Study of the scatter radiation in Digital Breast Tomosynthesis (DBT). Generally in DBT no scatter grid is used due to the low exposure per projection. Energy that maximizes the image quality parameter is not affected by scatter. High glandular percentage breast presents scatter-to-primary ratio (SPR) of 50%. Multi-scatter and secondary effects account for 30% of the total scatter radiation.